Editorial Preface - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak` (Idealogy Journal, 2021)
Overview of the Idealogy of Arts and Social Science by the Chief and Deputy Chief Editor. Keywords: Arts; Social Science